1993
DOI: 10.1210/jcem.77.5.8077303
|View full text |Cite
|
Sign up to set email alerts
|

Complex alteration of thyroid function in healthy centenarians.

Abstract: Several changes in thyroid function have been described in the elderly and largely attributed to concomitant nonthyroidal illness. The extent to which aging per se contributes to these changes remains to be elucidated, and scanty data are available in extremely old subjects. The present study was designed to focus on thyroid function during physiological aging, taking advantage of two groups of selected aged individuals: group A of healthy centenarians (n = 41; age range, 100-110 yr) and group B including heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 20 publications
2
43
1
4
Order By: Relevance
“…Healthy centenarians showed a lower prevalence of positive anti-thyroid autoantibody titer than elderly controls with a relatively low (7%) prevalence of sHT although the median serum FT3 level was lower than in each other group. Interestingly, median serum TSH level of centenarians was lower than in healthy elderly subjects, in whom however, was significantly lower than in young controls (Mariotti et al, 1993). This study did not resolve the question whether the decreased FT3 and TSH value observed in healthy centenarians, represents an adaptive mechanism to reduced metabolic homeostasis or a protective condition in ageing.…”
Section: Thyroid Function and Ageingcontrasting
confidence: 56%
See 2 more Smart Citations
“…Healthy centenarians showed a lower prevalence of positive anti-thyroid autoantibody titer than elderly controls with a relatively low (7%) prevalence of sHT although the median serum FT3 level was lower than in each other group. Interestingly, median serum TSH level of centenarians was lower than in healthy elderly subjects, in whom however, was significantly lower than in young controls (Mariotti et al, 1993). This study did not resolve the question whether the decreased FT3 and TSH value observed in healthy centenarians, represents an adaptive mechanism to reduced metabolic homeostasis or a protective condition in ageing.…”
Section: Thyroid Function and Ageingcontrasting
confidence: 56%
“…The relative small number of epidemiological studies with inappropriate statistical power, and the lack of large prospective randomized trials directed to evaluate the therapeutic effect and impact on survival of hormonal therapy in mild thyroid impairment, does not allow to conclude whether mild thyroid impairment is a favorable phenotype or a negative clinical condition, especially in older people. An age-dependent thyroid dysfunction (particularly hypothyroidism) has been well documented in the elderly, including the oldest-old population (>85 yr) (Helfand et al, 2004;Mariotti et al, 1993). An interesting study focused on thyroid function during physiological ageing was carried out by Mariotti et al (1993).…”
Section: Thyroid Function and Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid disorders in the elderly are not rare, but they frequently remain undiagnosed because their clinical symptoms are hardly noticeable and frequently changed or masked by concomitant illnesses and medications [23,25]. Acute diseases inhibit the peripheral conversion of T4 reducing the level of T3, at the same time increasing the concentration of the biologically inactive form of T3, so-called reverse triiodothyronine (rT3) [21,26,27,28,29]. Changes in the metabolism of thyroid hormones without diagnosable thyroid diseases are referred to as non-thyroidal illness syndrome (NTIS), euthyroid sick syndrome (ESS) or sick euthyroid syndrome (SES).…”
Section: Tarczycamentioning
confidence: 99%
“…Choroby o ciężkim przebiegu hamują konwersję obwodową T4, zmniejszając stężenie T3 i równocześnie podwyższając stężenie biologicznie nieaktywnej postaci T3, tzw. odwrotnej trijodotyroniny (rT3) [21,25,26,27,28,29]. Zmiany w metabolizmie hormonów tarczycy bez uchwytnych chorób tarczycy określa się mianem non-thyroidal illness syndrome (NTIS), euthyroid sick syndrome (ESS) lub sick euthyroid These syndromes occur in patients with myocardial infarction, sepsis, diabetic coma, following extensive thermal injuries, major surgical procedures and organ transplants.…”
Section: Tarczycaunclassified